"All‐in‐One" Gel System for Whole Procedure of Stem‐Cell Amplification and Tissue Engineering. Issue 16 (5th March 2020) - He, Qiulin; Liao, Youguo; Zhang, Jingwei; Yao, Xudong; Zhou, Wenyan; Hong, Yi; Ouyang, Hongwei
Abstract: Microsphere (MS)‐based systems provides great advantages for cell expansion and transplantation due to their high surface‐to‐volume ratio and biomimetic environment. However, a MS‐based system that includes cell attachment, proliferation, passage, harvest, cryopreservation, and tissue engineering together has not been realized yet. An "all‐in‐one" gel MS‐based system is established for human adipose‐derived mesenchymal stem cells (hADSCs), realizing real 3D culture with enhanced expansion efficiency and simplified serial cell culture operations, and construction of macrotissues with uniform cell distribution and specific function. A 3D digital light‐processing technology is developed to fabricate gel MSs in an effective way. The printed MSs present a suitable environment with rough surface architecture and the mechanical properties of soft tissues, leading to high cell viability, attachment, proliferation, activity, and differentiation potential. Further, convenient standard operation procedures, including cell passage, detachment, and cryopreservation, are established for cell culture on the gel MSs. Finally, hADSCs‐loaded gel MSs form macrotissues through a "bottom‐up" approach, which demonstrates the potential applications for tissue engineering. These findings exhibit the feasibility and beauty of "all‐in‐one" stem cell culture and tissue engineering system. Abstract : An "all‐in‐one" gel‐based system for stem cell amplification and tissue engineering is developed through the use of a layer‐by‐layer 3D digital light‐processing technology. The system provides enhanced expansion efficiency (cell attachment and proliferation), simplified serial cell‐culture operations (cell passage, preservation, and harvest), and tissue engineering.